Changing motivations of the special constable: a qualitative analysis of the role of organisational experience in retaining satisfaction and commitment - Ramshaw, Pauline (Policing and society, 2020)
In a climate of diminishing resources, securing a prolonged commitment to volunteer from special constables is an aspirational goal for police organisations. This paper moves beyond traditional egoistic and altruistic standpoints that draw people into this unpaid role, to consider ongoing decision-making processes that occur in post, which can shape a long-term career path as an unpaid volunteer special constable. Rich narratives, drawn from semi-structured interviews with volunteer special constables, capture a unique and original perspective largely absent from discussion around special constable motivation. Data and findings speak to important gaps in existing knowledge about how and why orientations to volunteering can change over the duration of a special constable’s service, resulting from organisational rather than policing experiences. Findings serve as a timely reminder that while it is important to develop deeper understandings of motives to becoming a special, so too is the significance of furthering knowledge on ways in which the experience of being a special constable within the police organisation can work to sustain commitment, motivation and thus encourage retention.